Análise geocológica direcionada ao planejamento e gestão ambiental da Provincia de Sofala - Moçambique. - Pacheco, Júlio Acácio António (2014)
This research focuses on the Geoecological Analysis directed the Environmental Management and Planning of Sofala province - Mozambique. The presented study aims to contribute with proposals to establish guidelines for improving environmental planning and management in communities of Sofala Province, central region of Mozambique. The research was developed in the period between 2011 - 2013, with a theoretical-methodological approach based on qualitative research structured in geossystem thought, ecodynamics, geoecological landscape in expository and descriptive form. Data collection involved the execution of unstructured interviews with individuals in situ of the study area, articulate analysis of photographic documentation, systematic records of field observations, literature and documents in government agencies of Mozambique, as well as reading and interpreting cartographic maps and data. An analysis was materialized on a regional scale, the natural physical and socioeconomic conditions, identifying different forms of exploitation of natural resources, as well as its direct and immediate impacts on the environment, which including timber extraction, fisheries, mining, charcoal production, their techniques, motivations and consequences. The process analysis of geoenvironmental components and socioeconomic conditions also enabled the identification, delimitation of compartments geoecological constants in Serranos areas, plateaus or sopes, Depressions and Plains areas. Based on the diagnosis, types of use and predominant occupation were grouped in parks /reserves, game reserves, farm lands of future agricultural, forest concessions, farm mustang, mining and subsistence communities. Regarding the established ecodynamic balance by dynamic morphogenesis pedogenesis, we determined the occurrence of unstable, stable geoecological compartments and transition tendency to instability. Still presents itself as a contribution resulting from the investigation, the proposed functional geoecological zoning regionally that determined suitability of use and preservation in total protection zone; partial protection zone; plant extraction area; mining area; urban expansion area; agricultural production area, family agro ecological production area and environmental recovery zone